Employees' reactions to IT-enabled process innovations in the age of data analytics in healthcare. Issue 3 (5th June 2017) - Bala, Hillol; Venkatesh, Viswanath
Abstract : Purpose: Interorganizational business process standards (IBPS) are IT-enabled process specifications that standardize, streamline, and improve business processes related to interorganizational relationships. There has been much interest in IBPS as organizations from different industries implement these process standards that lead to successful organizational outcomes by integrating and standardizing intra- and inter-organizational business processes. These process standards enable data analytics capabilities by facilitating new sources of interorganizational process data. The purpose of this paper is to unearth employees' reactions to a new type of supply chain process innovations that involved an implementation of new IBPS, a supply chain management (SCM) system, and associated analytics capabilities. Design/methodology/approach: The authors gathered and analyzed qualitative data for a year from the employees of a healthcare supplier, a high-tech manufacturing organization, during the implementation of a SCM system and RosettaNet-based IBPS. Findings: In what the authors termed the initiation stage, there was quite a bit of confusion and unrest among employees regarding the relevance of the new process standards and associated analytics capabilities. With the passage of time, in the institutionalization stage, although the situation improved slightly, employees found workarounds that allowed them to appropriate just part of specific processes and the analytics capabilities. Finally, once routinized, employees felt comfortable in the situation but still did not appropriate the new supply chain processes faithfully. Overall, employees' reactions toward the SCM system and associated analytics capabilities were different from their reactions toward the new business processes. Originality/value: The paper contributes to the literature by offering novel insights on how employees react to and appropriate process innovations that change their work processes.